Single‐source dual‐layer amorphous IGZO thin‐film transistors for display and circuit applications. Issue 3 (10th June 2013) - Nag, Manoj; Chasin, Adrian; Rockele, Maarten; Steudel, Soeren; Myny, Kris; Bhoolokam, Ajay; Tripathi, Ashutosh; van der, Bas; Kumar, Abhishek; van der, Jan‐Laurens; Genoe, Jan; Li, Flora; et al.
Abstract In this study, the authors report on high‐quality amorphous indium–gallium–zinc oxide thin‐film transistors (TFTs) based on a single‐source dual‐layer concept processed at temperatures down to 150°C. The dual‐layer concept allows the precise control of local charge carrier densities by varying the O2/Ar gas ratio during sputtering for the bottom and top layers. Therefore, extensive annealing steps after the deposition can be avoided. In addition, the dual‐layer concept is more robust against variation of the oxygen flow in the deposition chamber. The charge carrier density in the TFT channel is namely adjusted by varying the thickness of the two layers whereby the oxygen concentration during deposition is switched only between no oxygen for the bottom layer and very high concentration for the top layer. The dual‐layer TFTs are more stable under bias conditions in comparison with single‐layer TFTs processed at low temperatures. Finally, the applicability of this dual‐layer concept in logic circuitry such as 19‐stage ring oscillators and a TFT backplane on polyethylene naphthalate foil containing a quarter video graphics array active‐matrix organic light‐emitting diode display demonstrator is proven.